Low-loss austempered ductile iron gears: experimental evaluation comparing materials and lubricants - Magalhães, Luís (2014)
An experimental study to evaluate the power dissipation of gears was performed. Three low-loss gear models were manufactured using standard 20° pressure angle tools. Austempered ductile iron (ADI) and 20MnCr5 carburized steel gears were tested in an FZG gear test machine using mineral, ester and polyalphaolephine (PAO)-based oils. The results compare power dissipation, the influence of different tooth flank geometries, materials and lubricants. This work concludes that conventional power-transmission gears can be replaced by these improved and more efficient low–loss models, which can be produced using common tools and that steel gears can be successfully replaced by austempered ductile iron gears.